INCREASING NEED FOR POLITICAL GOVERNANCE IN PROVIDING SUSTAINABLE DEVELOPMENT OF SOCIETY (Scientific journal of the Fergana State University, 2024)
This article examines the highest level of the hierarchy of management, covering both daily management andthe burden of responsibility for it, or rather the idea of a person, society, community in most cases of life and activity,each of which represents a separate but interrelated aspect, a step.